METHODOLOGY FOR DIRECTING LEARNERS TOWARD INNOVATIVE ACTIVITIES IN A DIGITAL TRANSFORMATION ENVIRONMENT WITHIN THE COMPETENCY DEVELOPMENT SYSTEM (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This scientific article highlights the methodology of orienting learners towards innovative activities in the professional development system under conditions of digital transformation. It focuses on enhancing their digital competencies through the teaching of the pedagogical technologies module.